2013
DOI: 10.5897/jcab2013.0204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prostaglandin F2 treatment on semen characteristics of crossbred rams in the non-breeding season

Abstract: The aim of the present study was to evaluate the effects of administration of PGF 2 α on semen characteristics in crossbred rams in the non-breeding season. Twenty crossbred rams (Arkhar-Merino × Moghani and Arkhar-Merino × Ghezel) were randomly allocated into two equal groups. The experimental group received 7.5 mg IM of Estroplan (PGF2α analogue) and the control group received 1 ml of water soluble. A total number of eighteen ejaculates per ram were collected by artificial vagina twice a week 30 min followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
3
6
0
3
Order By: Relevance
“…Decreased motility after administration of PGF2α not only occurs in kacang goat but could also occur in other animals. This is in accordance with the statement of Capitan et al (1990), Masoumi et al (2011), and Olfati et al (2013). Capitan et al (1990) reported the motility of buffalo spermatozoa pretreatment, in treatment, and post-treatment were 43.19%; 45.46%; and 49.06%.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Decreased motility after administration of PGF2α not only occurs in kacang goat but could also occur in other animals. This is in accordance with the statement of Capitan et al (1990), Masoumi et al (2011), and Olfati et al (2013). Capitan et al (1990) reported the motility of buffalo spermatozoa pretreatment, in treatment, and post-treatment were 43.19%; 45.46%; and 49.06%.…”
Section: Resultssupporting
confidence: 90%
“…Failure in increasing spermatozoa concentrations in this study was likely due to the long interval (two days) between PGF2α administration and spermatozoa collection. In other studies, semen collection was carried out 30 minutes after PGF2α administration significantly improve the spermatozoa concentration (Kreider et al, 1981;Hashizume and Niwa, 1984;Mekonnen et al, 1989;Estienne and Harper, 2004;Olfati et al, 2013). However, in study conducted by Capitan et al (1990) who performed semen collection one hour after PGF2α administration and seven days after the last PGF2α injection (post treatment) did not able to increase spermatozoa concentration.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The optimal interval between prostaglandin PGF2α injection and ejaculation is around 30-60 minutes. This confirmed the report of Olfati et al (2013) which concluded that the best administration interval was 30 minutes while Capitan et al (1990) showed that some semen characteristics of the treatment group and posttreatment group (1 mg prostaglandin PGF2α) increased significantly at 1 hour compared to the control group.…”
Section: Resultssupporting
confidence: 88%
“…Interval antar perlakuan adalah satu minggu. Koleksi semen dilakukan 30 menit setelah penyuntikan PGF2α sesuai petunjuk Olfati et al (2013). Pola penyuntikan sampel disajikan pada Tabel 1.…”
Section: Penampungan Semenunclassified